2017
DOI: 10.1080/01634372.2017.1417342
|View full text |Cite
|
Sign up to set email alerts
|

Practitioners preferences of care coordination for older people: A discrete choice experiment

Abstract: These findings demonstrate the importance of organisations providing care coordination for older people receiving long-term funding. Further research is required to investigate the influence of service setting on practitioner preferences. This study explored practitioner preferences about the relative value of attributes of care coordination services for older people. A Discrete Choice Experiment (DCE) survey was used to identify the views of 120 practitioners from 17 services in England in 2015. The survey de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(43 citation statements)
references
References 31 publications
0
30
0
9
Order By: Relevance
“…Previous research has identified that a trusting relationship between the staff and the person with dementia and continuity of care with a limited number of staff visiting the same patient are critical for maintaining quality care for people with dementia. The same applies to sufficient time to spend in the patient's home (Gorska et al., 2013; Jansen et al., 2009; Jasper et al., 2018; Samus et al., 2018; Toot et al., 2013; Turjamaa et al., 2014). The results of our study, where staff experienced continuity of care (visiting the same patient) and enough time for each patient as important factors in the organization of homecare services for people with dementia, are consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has identified that a trusting relationship between the staff and the person with dementia and continuity of care with a limited number of staff visiting the same patient are critical for maintaining quality care for people with dementia. The same applies to sufficient time to spend in the patient's home (Gorska et al., 2013; Jansen et al., 2009; Jasper et al., 2018; Samus et al., 2018; Toot et al., 2013; Turjamaa et al., 2014). The results of our study, where staff experienced continuity of care (visiting the same patient) and enough time for each patient as important factors in the organization of homecare services for people with dementia, are consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…People with dementia in Norway often receive homecare services for many years and with frequent visits during a single day (Corbett & Williams, 2014). The assurance of receiving seamless homecare services that maintain continuity of care is important for both the patient, family members and the staff (Donnelly et al., 2017; Gorska et al., 2013; Jansen et al., 2009; Jasper et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was part of a broader mixed methods research project investigating the provision of care coordination for older people in the non-statutory sector in England. The study included: a scoping review of literature and policy (Abendstern et al 2018); a structured internet search of organisations in the non-statutory sector providing care coordination for older people (Jasper et al 2016) and a national survey of these organisations ; the development of a set of care coordination standards relating to both organisational and practice arrangements (Abendstern, et al 2016a) and fieldwork with a small number of organisations to explicate the range and content of care coordination activities undertaken, investigate the costs and validate the standards (Abendstern et al 2016b;Jasper et al 2017;Abendstern et al 2019). The work reported here is from the fieldwork stage of this project, specifically addressing staff activities, time use and cost.…”
Section: Introductionmentioning
confidence: 99%